Evaluation of Design and Analysis of Urban Stormwater Drainage System Using XP-SWMM - Binti Abd Razak, Nurul Nabeela Binti Abd Razak (Universiti Teknologi PETRONAS, 2018)
Since the human population has kept on increasing, urbanization has become the worldwide trend. This also resulted in increasing rate of impervious area and caused severe flooding around the world including Malaysia. In regards of that, the project is to design an urban storm water drainage system by using XP-SWMM. The area chosen for the study area is located at Jengka, Maran, Pahang. Furthermore. The drain was designed as swale drain in the majority area whereas suitable and the concrete drainage was used for culvert design. The objectives of this project are to evaluate and compare the drainage design by using simulation model and conventional method. The first step was designing the drain using the existing information by using the Excel Spreadsheet. For the simulation model, there are two simulations required which are the runoff and hydraulic simulation. For runoff simulation, the catchment data and rainfall information are required meanwhile the hydraulic simulation required data such as drainage size, slope and also land elevation. After running both simulation, the result was obtained and analysis regarding the project was made. The output from model simulation which is the peak discharge also was compared with the manual conventional method. From XP SWMM, the maximum runoff discharge was determined from each node the area was observe to have no area which is prone to flooding. As XP-SWMM software was used in this study, the software was found to be a very useful software where it can predict the area which is prone to have flood and also can be used to design the drainage in the best dimension.